Hubungan Konsumsi Alkohol dengan Kadar High Density Lipoprotein - Batara, Aditya N.; Pangkahila, Erwin; Polii, Hedison (eBiomedik, 2018)
Abstract: Alcohol consumption has some effect on myocardial infarction (heart attack), and could decrease low density lipoprotein (LDL) level as well as increase high density lipoprotein (HDL) level. This study was aimed to determine the relationship between alcohol consumption and HDL level. This was an analytical study with a cross sectional design. Subjects were students of Faculty of Social and Political Sciences at Sam Ratulangi University. Data were analyzed by using the Spearman correlation test (significancy <0.05). The results showed that 31 students were involved in this study. There were 26 students (83.87%) with normal HDL levels and 5 students (16.13%) with abnormal HDL levels. The Spearman test of the correlation between alcohol consumption (frequency, duration, and the amount of alcohol consumption) and HDL level showed the P values, as follows: P=0.256, P=0.410, and P=0.459. Conclusion: There was no correlation between alcohol consumption and HDL level.Keywords: alcohol, HDL levelsÂ Abstrak: Konsumsi alkohol diketahui memiliki efek terhadap infark miokard, penurunan kadar low density lipoprotein (LDL), dan peningkatan kadar high density lipoprotein (HDL). Penelitian ini bertujuan untuk mengetahui hubungan konsumsi alkohol dengan kadar HDL. Jenis penelitian ialah analitik dengan desain potong lintang. Subyek penelitian ialah mahasiswa Fakultas Ilmu Sosial dan Politik di Universitas Sam Ratulangi. Analisis data menggunakan uji korelasi Spearman dengan nilai signifikansi P<0,05. Hasil penelitian mendapatkan 31 mahasiswa laki-laki sebagai subyek penelitian. Subyek yang memiliki kadar HDL normal sebanyak 26 orang (83,87%) dan yang tidak normal sebanyak 5 orang (16,13%). Uji korelasi Spearman terhadap hubungan antara konsumsi alkohol (frekuensi konsumsi, lama konsumsi, jumlah konsumsi alkohol) dengan kadar HDL memiliki nilai P berturut-turut ialah P=0,256, P=0,410, dan P=0,459. Simpulan: Tidak terdapat hubungan bermakna antara konsumsi alkohol dengan kadar HDL.Kata kunci: alkohol, kadar HDL